Psychological and pedagogical conditions for the formation of the image of the future special educator - Koshzhanova, Gulshat; Ibragim, Kairat; Tusseyev, Mukhamejan; Gurbanova, Arzu (Institute of Advanced Engineering and Science, 2025)
In contemporary educational paradigms, the formation of a positive image of teachers plays a crucial role in students’ learning. However, the psychological and pedagogical conditions that contribute to the formation of the professional image of teachers have not been sufficiently investigated. The use of innovative teaching methods and effective communication strategies, are key to improving the professional image of teachers and can significantly improve teacher training in higher education institutions. The objective of this study is to investigate the impact of psychological and pedagogical factors on the professional image of special educators, assess the effectiveness of innovative teaching methods in the training process of teachers. The study was experimental in nature and employed a mixed-methods approach, incorporating both quantitative and qualitative data collection methods, including interviews and surveys. The experiment involved 200 participants (180 students and 20 teachers), randomly selected from three universities in Kazakhstan. The results indicated that innovative teaching methods significantly improved teachers’ perceptions of their professional image, evidenced by an increase in the average score of participants from 68.5 to 85.4 (p<0.001). Data analysis also revealed a positive correlation between the teacher’s image and factors such as the use of interactive technologies and communication strategies.